2005
DOI: 10.1007/s00449-005-0002-7
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maltose on dextran yield and molecular weight distribution

Abstract: Dextran synthesis has been studied since the Second World War, when it was used as blood plasma expander. This polysaccharide composed of glucose units is linked by an alpha-1,6-glucosidic bond. Dextransucrase is a bacterial extra cellular enzyme, which promotes the dextran synthesis from sucrose. When, besides sucrose, another substrate (acceptor) is also present in the reactor, oligosaccharides are produced and part of the glucosyl moieties from glucose is consumed to form these acceptor products, decreasing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(42 citation statements)
references
References 18 publications
3
37
0
2
Order By: Relevance
“…Statistical significance was evaluated by ANOVA and F test (Table 3) considering a confidence interval of 95%. All fitted models were statistically significant since F calculated [ F listed [16]. The regression coefficients were also good for all fitted models (R 2 [ 0.90).…”
Section: Discussionmentioning
confidence: 77%
“…Statistical significance was evaluated by ANOVA and F test (Table 3) considering a confidence interval of 95%. All fitted models were statistically significant since F calculated [ F listed [16]. The regression coefficients were also good for all fitted models (R 2 [ 0.90).…”
Section: Discussionmentioning
confidence: 77%
“…The crude fermented broth free of cells (100 lL) was mixed with 400 lL of a 10% (w/v) sucrose solution in an acetate buffer pH 5.2 (20 mM containing 0.05 g/L of CaCl 2 ) and then incubated for 1 h at 30°C. The reaction was stopped adding three volumes of ethanol 96% (v/v) [18]. The enzyme activity was expressed in DSU/10 lL (dextransucrase unit/lL).…”
Section: Enzyme Activity Assaymentioning
confidence: 99%
“…Rodrigues [21] employed maltose as acceptor to study dextran synthesis in the submerged culture of Leuconostoc mesenteroides B512F. The author found that maltose was unable to control and reduce dextran molecular weight distribution and suggested that acceptor reaction could occur at a unique and separated site.…”
Section: Resultsmentioning
confidence: 98%